The fanzine as a pedagogical strategy to strengthen the social skills of eight grade students in the Colegio Integrado Nuestra Señora de la Paz - Téllez Quintero, Luisa María Aurora; Pérez Quijano, Angélica (Rastros Rostros, 2024)
This scientific article shows the utility of the fanzine as a pedagogical strategy through a detailed exposition of the investigative process carried out during the three educational practices that are part of the Bachelor’s Degree in Literature and Spanish Language at the Universidad Industrial de Santander. The practices were conducted at Colegio Integrado Nuestra Señora de la Paz, a rural institution located in the Tienda Nueva district of Betulia, Santander. At the end of 2022, the first observation trips of students were made, eventually leading to the planning of the interventions. Then, in 2023, the teaching mediations and their analysis were conducted. Initially, the characteristics of the class dynamics and learning identified during the observation phase are presented. Some problems were found in both cognitive formation and social interactions among students. Following the identification of these problems, the process of creating a solution is presented, starting with the creation of didactic sequences and culminating with their intervention in the classroom. Finally, the article presents the collected results and the progress in the aforementioned aspects. Additionally, it includes the general conclusions of the work carried out during the three pedagogical practices and the improvements that could be made to enhance the relevance of the course in the students’ education.
Keywords: habilidades sociais; sequência pedagógica; análise